PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN PADA BANK NAGARI CABANG PASAR RAYA KOTA PADANG - JOKO, MUHAMMAD (Jurnal Marketing, 2018)
The background of this study aims to determine the effect of intellectual intelligence, emotional intelligence and spiritual intelligence tehadap performance of Bank Nagari employees Branch of Pasar Raya Kota Padang. Population in this research is employees of bank nagari branch of highway outside branch leader. By using purposive sampling method. Of the 64 employees, only 63 people were sampled, because of using certain criteria or sample criteria that have been set.The result of research by using multiple linear analysis showed that intellectual intelligence variable (X1) had no significant effect, emotional intelligence (X2) had significant and significant and Spiritual Intelligence (X3) had no significant effect on employee performance (Y).